Self-regulation sets standards in echocardiography accreditation - Chambers, John B. (SA Heart Journal, 2017)
he British Society of Echocardiography (BSE) and the European Association of Echocardiography (EAE) run voluntary accreditation programmes both for individuals and echocardiography laboratories with the aim of elevating standards both ways. In this commentary John Chambers discusses the evolution of accreditation and the development of standards of care in echocardiography in the UK and Europe. As past president of the BSE he has been instrumental in the process of developing training programmes and accreditation in echocardiography.